ENVIRONMENTAL THINKING IN THE FOLKLORE OF MIZORAM - Verma, Nidhi (International Journal of Research -GRANTHAALAYAH, 2024)
Mizoram is made up of two words. ’Mizo’ literally means mountain dweller. This word is made up of the combination of ’Mi’, ’Zo’ and ’Ram’. ’Mi’ means ’people’, ’Zo’ means mountain and ’Ram’ means land. That is, the land where mountain people live. According to the second belief, the word ’Mizoram’ is made up of the combination of ’Mizo’ and ’Ram’. ’Mizo’ means ’Mizo community’ and ’Ram’ means ’land’. Mizoram is situated in a beautiful environmental area. It is a state full of natural wealth and very close to the environment. The Mizo people have a very close and deep relationship with the environment. The place where the Mizo tribe is currently settled used to be a dense forest. The Mizo people started a new society and culture by cutting down these dense forests of the mountains. Their ancestors lived in harmony with nature and environment. Their civilization was born and grew up in the lap of this environment. The main focus of Mizo folklore is nature and environment. Mizo society and culture originated and developed with the environment. This is the reason why the concept of Mizo folklore is built around the environment. Mizoram is situated in the mountains and very good sources of water are found at the foot of these mountains, so there are many small and big rivers here. The story based on the formation of mountains and rivers is expressed in Mizo folklore.